Pengaruh Kualitas Pelayanan Publik Dan Fasilitas Pelayanan Terhadap Kepuasan Masyarakat - Elisatul Rochmah; Brillian Rosy (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2022)
The purpose of this paper is to find out the effect of the quality of public services and facilities on the satisfaction of the people of the Deket sub-district in recording E-KTP. This study uses a descriptive method through a quantitative approach technique. Sampling using non-probability purposive sampling technique. The number of samples is 35 respondents. The distributed of questionnaire was carried out to collect research daya, with closed questionnaire questions.The results instrument uses multiple linear resgression, coefficient of determination, t-test and F-test. From the results of this study, it can be concluded that the quality of public services and service facilities has a positive and significant effect on community satisfaction. Based on the results of the study, it is expected that the employees of the Deket District office can improve the quality of public services and increase the use of service facilities to be effective in order to increase the satisfaction of the people of Deket District in the E-KTP service.